Beneficial Effects of Minocycline and Botulinum Toxin–Induced Constraint Physical Therapy Following Experimental Traumatic Brain Injury. (November 2013) - Lam, Tina I.; Bingham, Deborah; Chang, Ting Ju; Lee, Chih Cheng; Shi, Jian; Wang, Dongmin; Massa, Stephen; Swanson, Raymond A.; Liu, Jialing
Background . Effective recovery from functional impairments caused by traumatic brain injury (TBI) requires appropriate rehabilitation therapy. Multiple pathways are involved in secondary injury and recovery suggesting a role for multimodal approaches. Objective . Here, we examined the efficacy of the anti-inflammatory agent minocycline and botulinum toxin (botox)–induced limb constraint with structured physical therapy, delivered alone or in combination, after a severe TBI produced by a controlled cortical impact in rats. Methods . Minocycline was administered at 25 mg/kg daily for 2 weeks beginning 1 day after TBI or sham surgery. For constraint/physical therapy, botox-type A was injected into the nonaffected forearm muscle 1 day after injury and 2 weeks of physical therapy commenced at 5 days after injury. Functional evaluations were conducted 8 weeks after injury. Results . Minocycline, either as a monotherapy or as combination treatment with botox/physical therapy significantly reduced impairments of spatial learning and memory in the water maze test, whereas botox/physical therapy reduced forelimb motor asymmetry and improved manual dexterity in the cylinder and vermicelli handling tests, A synergistic effect between the 2 treatments was observed when rats performed tasks requiring dexterity. Inflammation was attenuated in the peri-contusion cortex and hippocampus in all TBI groups receiving mono or combination therapies, though there was no significant difference in lesion size among groups. Conclusion . These data provide a rationale for incorporating anti-inflammatory treatment during rehabilitation therapy.